ANALYSIS OF STUDENTS' MISCONCEPTIONS USING A THREE-TIER DIAGNOSTIC TEST ON GEOMETRIC OPTICS MATERIAL AT THE JUNIOR HIGH SCHOOL LEVEL - Alwan Hadi; Rudi Purwanto (INERCYS: Institute of Educational, Research, and Community Service, 2025)
Geometric optics is an important topic in junior high school physics education, but it often causes conceptual difficulties for students. Many students experience misconceptions due to limitations in understanding abstract physical phenomena such as reflection, refraction, and image formation. This study aims to analyze the form and level of students' misconceptions in geometric optics using the Three-Tier Diagnostic Test instrument. This study is a quantitative descriptive study using a survey approach. The instrument used is a three-tier diagnostic test specifically designed to identify students' conceptual understanding, consisting of 15 questions covering three aspects: multiple-choice answers, conceptual reasoning, and confidence level. Data were collected by distributing the test to 120 eighth-grade students from three junior high schools who had studied optical concepts. Data analysis techniques used classification based on the Treagust model, which distinguishes between students who understand the concept, have misconceptions, guess, have limited understanding, and do not understand. The results of the study show that 46% of students have misconceptions, 31% understand the concept correctly, 12% guess, 7% do not understand, and 4% have limited understanding. The highest misconceptions were found in the sub-topic of light refraction (62%), followed by shadows on lenses (55%) and curved mirrors (51%). Additionally, 67% of students answered with high confidence despite their incorrect answers, indicating that misconceptions are deeply rooted. It can be concluded that misconceptions remain a serious issue in geometric optics learning, and the use of the Three-Tier Diagnostic Test has proven effective in comprehensively identifying and mapping misconceptions. These findings provide a foundation for developing more targeted diagnostic-based learning strategies to enhance students' conceptual understanding.